Mixed-methods study of university students' perceptions of COVID-19 and media consumption from March 2020 -April 2022. - Madeleine Mant; Asal Aslemand; Andrew Prine; Alyson Holland (Public Library of Science (PLoS), 2024)
Longitudinal mixed-methods research is necessary to understand the changing dynamics of pandemic perceptions, the adoption of health behaviours, and use of media during a public health emergency. During the first two years of the COVID-19 pandemic, we used a mixed-methods approach to survey young adults attending a large Canadian public university. Six online convenience survey samples were collected (Spring 2020, Summer 2020, Fall 2020, Spring 2021, Fall 2021, Spring 2022) (n = 4932) and 110 semi-structured interviews were conducted. Female gender was associated with higher perceptions of severity, susceptibility, and the adoption of new health behaviours. Perceptions of severity and anxiety/fear about contracting COVID-19 after reading/hearing a news report decreased overall over time, while perceptions of susceptibility increased through time overall. Social media was the most used form of media and was the form of media that participants judged to make them feel most anxious/fearful about contracting COVID-19. Those who felt anxious after hearing a COVID-19 news report were 8.43 times more likely to judge COVID-19 as severe and 2.07 times more likely to judge their own susceptibility as high. Interviews revealed perceptions of information overload, passive information intake, and a narrowed geographical focus over time. The decrease in judgements of COVID-19 severity with the accompanying increase in judgements of susceptibility over the first two years of the pandemic demonstrate the dynamics of changing pandemic attitudes. Health communication efforts targeting university students in future major health events need to consider these shifting dynamics and ensure that health information distributed via social media meets the needs of university students.